Effectiveness of simulation learning program for mastering public health nursing skills to enhance strength of community: A quasi-experimental design. (July 2020) - Okamoto, Reiko; Gouda, Kayoko; Koide, Keiko; Tokimasa, Mai; Kageyama, Masako; Iwamoto, Saori; Shiomi, Misa; Kusano, Emiko; Tanaka, Miho; Kiya, Misaki; Tada, Aoki; Koetaka, Hanayo
Abstract: Purpose: The purpose of this study is to develop a simulation learning program for mastering public health nursing skills to enhance strength of community, and to verify its effectiveness. Methods: The program is one-day session to master the skills from three exercises. This study adopts a quasi-experimental design. We selected unbiased 34 participants in intervention group and 30 participants in control group, and conducted self-administered questionnaire surveys at three points in time: pre, post 1 and post 2. Three tools were used to measure the required outcome. For the outcome evaluation, we calculated the changes in the mean value of each tool between pre and post 1 and between pre and post 2, and compared them between the two groups. Results: The change of intervention group in the total score at the post 1 stage from the pre stage was significantly higher than control group regarding each of the scales ( P  < .05). Conclusions: The program was found to be effective in upgrading the skills of less-experienced public health nurses to enhance strength of community.